2007
DOI: 10.1002/art.22469
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and validation of the patient acceptable symptom state (PASS) in patients with ankylosing spondylitis

Abstract: Objective. The Patient Acceptable Symptom State (PASS) constitutes an absolute level of patient well-being and represents an ambitious target for disease management. We explored contributors to PASS, validated the PASS concept, and assessed thresholds of self-reported outcomes below which patients considered themselves in PASS. Methods. Patients with ankylosing spondylitis completed a questionnaire that included self-reported assessments of pain, fatigue, disease activity, function, patient global, quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 16 publications
6
110
1
3
Order By: Relevance
“…For example, the ASQoL score of patients who satisfied the FM criteria (mean 13.1) indicated worse quality of life than the level deemed acceptable by patients (ASQoL score of 8.0) (31). Moreover, according to reference centile charts of the BASDAI, patients who met the criteria for FM had a mean BASDAI score between the 75th and 90th centiles (32).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ASQoL score of patients who satisfied the FM criteria (mean 13.1) indicated worse quality of life than the level deemed acceptable by patients (ASQoL score of 8.0) (31). Moreover, according to reference centile charts of the BASDAI, patients who met the criteria for FM had a mean BASDAI score between the 75th and 90th centiles (32).…”
Section: Discussionmentioning
confidence: 99%
“…This approach identifies the cut-off point corresponding to the 75th percentile of the scores for improvement in patients who report an important improvement by the anchoring question. Applying receiver operating characteristic (ROC) curves allows for choosing the threshold that is the best compromise between sensitivity and specificity for each outcome criterion 7 8…”
Section: The Concepts Of MCII and Mcidmentioning
confidence: 99%
“…One cross-sectional study described the validation of the PASS in AS according to reported flare status, expressed need to see the physician, attainment of ASAS partial remission, and PASS contribution to QOL (5). A second study showed that more patients with active AS who were ASAS20 responders following treatment with adalimumab achieved the PASS compared with ASAS20 nonresponders to adalimumab (6).…”
Section: Introductionmentioning
confidence: 99%
“…Significantly more adalimumab-treated patients reported achievement in the PASS compared with placebo-treated patients, indicating excellent discriminant capacity. There has also been considerable interest in defining the PASS concept according to thresholds for the patient self-reported outcomes (PROs) in AS (5)(6)(7)(8). However, these estimates have varied in different reports and it is unclear whether these variations reflect study design variability (cross-sectional versus prospective) or other unknown factors.…”
Section: Introductionmentioning
confidence: 99%